Prevalence and risk factors of cognitive impairment in Chinese patients with hypertension: a systematic review and meta-analysis - Xie, Cheng; Zhong, Dongling; Zhang, Yue; Liu, Xiaobo; Zhang, Lili; Luo, Xiao; Gong, Yimeng; Jiang, Wei; Jin, Rongjiang; Li, Juan (Frontiers in Neurology, 2024)
Background: Cognitive impairment is prevalent in Chinese patients with hypertension, however, current evidence regarding the prevalence and risk factors is required to be synthesized.This systematic review and meta-analysis aimed to evaluate the prevalence and risk factors of cognitive impairment in Chinese patients with hypertension.Methods: Two reviewers independently searched PubMed, Web of Science, Embase, The Cochrane Library, CNKI, CBM, Wanfang database, and VIP database from their inceptions to June 7th, 2023. The gray literature and the reference lists of the included studies were also manually retrieved. Moreover, we also independently performed the eligibility screening, data extraction, and data synthesis. The primary outcome was the prevalence of cognitive impairment in Chinese patients with hypertension, while the secondary outcomes were the risk factors of cognitive impairment in patients with hypertension. R (version 4.0.3) was used for data synthesis.Eighty-two studies involving 53,623 patients with hypertension were included in this metaanalysis. The pooled prevalence of cognitive impairment in patients with hypertension was 37.6% (95% CI: 33.2%-42.2%). Twelve risk factors, involving advanced age (r=-0.34, 95% CI: -0.45, -0.21),